2021
DOI: 10.1002/mc.23280
|View full text |Cite
|
Sign up to set email alerts
|

Germline MC1R variants and frequency of somatic BRAF, NRAS, and TERT mutations in melanoma: Literature review and meta‐analysis

Abstract: Germline variants of the melanocortin‐1‐receptor (MC1R) gene are the most common genetic trait predisposing to cutaneous melanoma (CM). Here, we performed a literature review and meta‐analysis of the association between MC1R gene variants and the frequency of somatic mutations of the BRAF, NRAS, and TERT genes in CM patients. We included studies published until January 2020 in MEDLINE, EMBASE, Ovid Medline, and two grey literature databases. Random effect models were used to pool study‐specific estimates into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…An additive model counting both R and r alleles gave a slightly better fit than a model counting only R alleles, implying that r alleles also affect age at onset. Multivariable regression analysis showed that somatic BRAF mutation and germline MC1R genotype are independently associated with age at onset, which is in line with MC1R genotype not being significantly associated with BRAF mutations (χ 2 , P = 0.74), confirming a meta-analysis ( 63 ).…”
Section: Resultssupporting
confidence: 61%
“…An additive model counting both R and r alleles gave a slightly better fit than a model counting only R alleles, implying that r alleles also affect age at onset. Multivariable regression analysis showed that somatic BRAF mutation and germline MC1R genotype are independently associated with age at onset, which is in line with MC1R genotype not being significantly associated with BRAF mutations (χ 2 , P = 0.74), confirming a meta-analysis ( 63 ).…”
Section: Resultssupporting
confidence: 61%
“…The difference in feather color in chickens is mainly affected by the production and transformation of melanin, and MC1R plays an important role in this process ( Zhang et al, 2017 ; Khumpeerawat et al, 2021 ; Schwochow et al, 2021 ). MC1R is a highly polymorphic gene, and more than 200 variants have been found ( Zanna et al, 2021 ). Some studies have shown that MC1R mutations or base substitutions can affect various phenotypes of feather color in chickens ( Liu et al, 2010 ; Oh et al, 2010 ; Kim and Production 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In chickens, the E locus encodes the MC1R protein consisting of 314 amino acids. The gene is located on chromosome 11 and has a long 945 bp CDS region ( Kabir et al, 2020 ; Zanna et al, 2021 ). Previous studies have shown that MC1R plays a key role in the regulation of eumelanin (black/brown) and phaeomelanin (red/yellow) feather pigments ( Robbins et al, 1993 ; Jackson 1997 ).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, MC1R variants may substantially increase the penetrance of CDKN2A mutations and the risk of melanoma in affected families, particularly multiple MC1R variants and red hair color variants [ 64 ]. Identifying polymorphisms and mutations of the MC1R gene would enable a better understanding of melanoma susceptibility and potential treatments [ 65 - 67 ].…”
Section: Genes That Increase the Risk Of Melanomamentioning
confidence: 99%